Effects of ketamine and midazolam on emergence agitation after sevoflurane anaesthesia in children receiving caudal block: a randomized trial - Ozcan,Ayse (2014)
Background and objectives: Emergence agitation is a common postanaesthetic problem in children after sevoflurane anaesthesia. We aimed to compare the effects of ketamine and midazolam administered intravenously, before the end of surgery, for prevention of emergence agitation in children who received caudal block for pain relief under sevoflurane anaesthesia. Methods: 62 American Society of Anesthesiologists patient classification status I children, aged 2–7 years, scheduled for inguinal hernia repair, circumcision or orchidopexy were enrolled to the study. Anaesthesia was induced with sevoflurane 8% in a mixture of 50% oxygen and nitrous oxide. After achieving adequate depth of anaesthesia, a laryngeal mask was placed and then caudal block was performed with 0.75 mL kg−1, 0.25% bupivacaine. At the end of the surgery, ketamine 0.25 mg kg−1, midazolam 0.03 mg kg−1 and saline were given to ketamine, midazolam and control groups, respectively. Agitation was assessed using Paediatric Anaesthesia Emergence Delirium scale and postoperative pain was evaluated with modified Children's Hospital of Eastern Ontario Pain Scale. Results and conclusions: Modified Children's Hospital of Eastern Ontario Pain Scale scores were found higher in control group than in ketamine and midazolam groups. Paediatric Anaesthesia Emergence Delirium scores were similar between groups. Modified Children's Hospital of Eastern Ontario Pain Scale and Paediatric Anaesthesia Emergence Delirium scores showed a significant decrease by time in all groups during follow-up in postanaesthesia care unit. The present study resulted in satisfactory Paediatric Anaesthesia Emergence Delirium scores which are below 10 in all groups. As a conclusion, neither ketamine nor midazolam added to caudal block under sevoflurane anaesthesia did show further effect on emergence agitation. In addition, pain relief still seems to be the major factor in preventing emergence agitation after sevoflurane anaesthesia.